Community-Engaged Research: Exploring a Tool for Action and Advocacy. Issue 4 (7th August 2020) - Wright, Naomi M.; Olomi, Julie M.; DePrince, Anne P.
ABSTRACT: Trauma psychologists seeking to engage in evidence-based advocacy and action may benefit from methods that prioritize public problem solving. Community-engaged research (CEnR) is one such method, characterized by reciprocal and mutually beneficial partnerships between academic researchers and community organizations to address public problems. The CEnR framework is designed and implemented in the context of researcher-community partnership; as such, the findings from this approach promise to be responsive to the real-world concerns of communities seeking to address trauma. This manuscript first articulates the rationale for CEnR in evidence-based advocacy and action. Next, we provide illustrations from our research team's CEnR focus on access to victim service and legal information following interpersonal traumas. We describe how CEnR positioned our team to be responsive in a quickly evolving sociopolitical context while providing data needed for community partners and trauma researchers alike to advocate for survivors and victim services. With this example as a jumping-off point, we discuss potential systemic changes that could foster increased use of CEnR strategies to address trauma-related problems in our communities.